Komedya de Baler - Almario, Virgilio S.; Yglopaz, Anna Maria M.; Kilates, Marne; Pleguezuelos, Fernando Ramos; National Historical Commission (Philippines). ([Manila] Pambansang Komisyon sa Kasaysayan ng Filipinas, 2012)
On history and development of Komedya de Baler, the first national theater group of the Philippines.
Includes bibliographical references (page 123)
Keywords: Theater -- Philippines -- History; Komedya de Baler -- History